Design Strategies for Cellular Nanosponges as Medical Countermeasures - Shuyan Wang; Dan Wang; Mingxuan Kai; Wei-Ting Shen; Lei Sun; Weiwei Gao; Liangfang Zhang (BME Frontiers)
The interest in using therapeutic nanoparticles to bind with harmful molecules or pathogens and subsequently neutralize their bioactivity has grown tremendously. Among various nanomedicine platforms, cell membrane-coated nanoparticles, namely, “cellular nanosponges,” stand out for their broad-spectrum neutralization capability challenging to achieve in traditional countermeasure technologies. Such ability is attributable to their cellular function-based rather than target structure-based working principle. Integrating cellular nanosponges with various synthetic substrates further makes their applications exceptionally versatile and adaptive. This review discusses the latest cellular nanosponge technology focusing on how the structure–function relationship in different designs has led to versatile and potent medical countermeasures. Four design strategies are discussed, including harnessing native cell membrane functions for biological neutralization, functionalizing cell membrane coatings to enhance neutralization capabilities, combining cell membranes and functional cores for multimodal neutralization, and integrating cellular nanosponges with hydrogels for localized applications. Examples in each design strategy are selected, and the discussion is to highlight their structure–function relationships in complex disease settings. The review may inspire additional design strategies for cellular nanosponges and fulfill even broader medical applications.